2016
DOI: 10.1177/0333102416656118
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metabolism before and after external trigeminal nerve stimulation in episodic migraine

Abstract: Background and aimA recent sham-controlled trial showed that external trigeminal nerve stimulation (eTNS) is effective in episodic migraine (MO) prevention. However, its mechanism of action remains unknown. We performed 18-fluorodeoxyglucose positron emission tomography (FDG-PET) to evaluate brain metabolic changes before and after eTNS in episodic migraineurs.MethodsTwenty-eight individuals were recruited: 14 with MO and 20 healthy volunteers (HVs). HVs underwent a single FDG-PET, whereas patients were scanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 27 publications
1
59
0
1
Order By: Relevance
“…The maximum stimulation intensity for both treatment types is 16 mA. The precise mode of action is unknown but data from imaging studies based on FDG-PET and fMRI suggest functional changes in the orbitofrontal cortex and the rostral anterior cingulate cortex (20,21). the inherent shortcomings of a study without a sham group.…”
Section: External Trigeminal Nerve Stimulationmentioning
confidence: 99%
“…The maximum stimulation intensity for both treatment types is 16 mA. The precise mode of action is unknown but data from imaging studies based on FDG-PET and fMRI suggest functional changes in the orbitofrontal cortex and the rostral anterior cingulate cortex (20,21). the inherent shortcomings of a study without a sham group.…”
Section: External Trigeminal Nerve Stimulationmentioning
confidence: 99%
“…We have recently published the results of a fluoro-deoxyglucose (FDG)-PET study that analysed brain metabolism in 14 patients suffering from episodic migraine without aura before, immediately after one 20-min session and after a 3-months treatment period of daily 20-min sessions of supraorbital eTNS with the Cefaly ® (60Hz, 16mA) (44). Baseline FDG-PET revealed a significant hypometabolism of orbitofrontal (OFC), rostral anterior cingulate cortices (rACC) and middle temporal lobe, compared to a control group of healthy volunteers.…”
Section: Supra-segmental Mechanismsmentioning
confidence: 99%
“…A fluorodeoxyglucose positron emission tomography (FDG-PET) study revealed that SONS by Cefaly® device increased the activity of the limbic system, and the orbitofrontal and anterior cingulate cortices in EM without aura patients. These results indicate that the proposed mechanism of Cefaly® might be the modulation of the descending pain control system of the trigeminovascular nociceptor in the trigemino-cervical complex [11,12]. This type of trigeminal nerve stimulation was the first to obtain the Food and Drug Administration's (FDA) approval for migraine therapy [12] (Table 3).…”
Section: Introductionmentioning
confidence: 93%